Biological activity studies of Artocarpus heterophyllus Lam. leaves - Fernando, K.S.S.P.; Abeysekera, A.M.; Goonathilake, A.K.E.; Padumadasa, C.; Chandrika, U.G.; Choudhary, M.I. (Proceedings of Second International Conference on S ' . Natural Products Genomics and Drug Discovery, 23-24 June 2016 Galadari Hotel, Colombo, Sri Lanka, 2016)
Attached